THE CONCEPT OF COMMUNICATION OF THE PESULAP MERAH IN TACKLING OCCULT ALTERNATIVE MEDICINE ACCORDING TO THE PERSPECTIVE OF THE ISLAMIC RELIGION - M. Nashoihul Ibad; Novianto Puji Raharjo (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2022)
Occult alternative medicine is a treatment of human health using strange things that are not by reason or methods of treatment in scientific medicine. One of the figures who overcome supernatural medicine by dismantling the actions of shamans under the guise of ustad is the Pesulap Merah on his youtube account "PESULAP MERAH OFFICIAL". Does this research want to reveal how the concept of communication is carried out by the Pesulap Merah in tackling shamans under the guise of religion according to the perspective of Islam? The purpose of this study is to find out the concept of communication carried out by the Pesulap Merah in overcoming alternative occult medicine according to the perspective of Islam. The method used in this study is qualitative. The data source uses descriptive results from the observations of the Youtube channel as well as comments from netizens. The results of this study show that the concept of proselytizing communication carried out by the Pesulap Merah wants to reveal the action of occult alternative medicine under the guise of Islam so that people do not fall into misguidance.